2020
DOI: 10.1038/s41374-020-0406-7
|View full text |Cite|
|
Sign up to set email alerts
|

Pigs with δ-sarcoglycan deficiency exhibit traits of genetic cardiomyopathy

Abstract: Genetic cardiomyopathy is a group of intractable cardiovascular disorders involving heterogeneous genetic contribution. This heterogeneity has hindered the development of life-saving therapies for this serious disease. Genetic mutations in dystrophin and its associated glycoproteins cause cardiomuscular dysfunction. Large animal models incorporating these genetic defects are crucial for developing effective medical treatments, such as tissue regeneration and gene therapy. In the present study, we knocked out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…[95][96][97][98] In this regard, engineered nuclease-mediated genome editing provides opportunities to modify the genomes of large animals, thereby making them applicable to modeling of diseases such as inherited cardiovascular diseases. 93,94,[98][99][100][101][102][103] Heterozygous pigs carrying the HCM point mutation R723G in the porcine MYH7 gene displayed HCM pathologies, including mild cardiomyocyte disarray, malformed nuclei, MYH7 overexpression, and neonatal lethality. 104 Schneider et al 105 generated RBM20 gene-edited pigs carrying a pathogenic R636Q mutation found in DCM patients.…”
Section: Modeling Inherited Heart Diseases In Large Animalsmentioning
confidence: 99%
“…[95][96][97][98] In this regard, engineered nuclease-mediated genome editing provides opportunities to modify the genomes of large animals, thereby making them applicable to modeling of diseases such as inherited cardiovascular diseases. 93,94,[98][99][100][101][102][103] Heterozygous pigs carrying the HCM point mutation R723G in the porcine MYH7 gene displayed HCM pathologies, including mild cardiomyocyte disarray, malformed nuclei, MYH7 overexpression, and neonatal lethality. 104 Schneider et al 105 generated RBM20 gene-edited pigs carrying a pathogenic R636Q mutation found in DCM patients.…”
Section: Modeling Inherited Heart Diseases In Large Animalsmentioning
confidence: 99%
“…(2018) [ 114 ] SGCD SCNT TALEN Matsunari et al . (2020) [ 128 ] Cryopyrin-associated periodic syndrome NLRP3 SCNT CRISPR Li et al . (2020) [ 116 ] Diabetes INS SCNT CRISPR Cho et al .…”
Section: Recent Trends In Gene Editing In Pigsmentioning
confidence: 99%
“…Other advantages of the pig model are its similarities in physiology, metabolism, genomics, and proteomics to humans [7][8][9][10]. Genetically modified pig disease models, such as the genetic cardiomyopathy model, have also been developed [11]. The current review updates the contributions of large animal models for research of cardiovascular medicine, especially focusing on the utility of pig models.…”
Section: Introductionmentioning
confidence: 99%